The Students’ Perceptions of the Strategies in the Process Approach - Eliwarti Eliwarti; Nooreiny Maarof (Education Administration Study Program, School of Postgraduate Studies, Universitas Riau, 2017)
The main objective of this study was to examine the students’ perceptions of the strategies in theProcess Approach. The subjects were 30 English Department students of Riau University taughtusing Process Approach. A set of questionnaire and semi-structured interview were used to collectthe data. The level of perceptions was differentiated into three: Highly Positive, Positive andNegative. The results showed that all students had Positive and Highly Positive level of perceptionand no students had Negative perception of the strategies in the Process Approach. From the resultsof the interview, five categories were found. All of them reported positive opinions on the ProcessApproach and considered the editing and revising strategies as most useful. Besides, they statedthat the steps in Process Approach were more systematic, specific, comfortable, more meaningfuland livelier than other approaches. They all perceived that their writing performance had improvedafter the Process Approach intervention. The area of improvements were in collecting ideas,editing strategy, choice of words and the way how to write an essay. They also suggested on theapplication of the Process Approach for other writing classes. The findings from the interviewswere in line with the findings from the questionnaire which revealed that students had favorableperceptions of the Process Approach. In light of these findings, it can be suggested that the ProcessApproach has the potential to be used as alternative instructional tools to improve students’ writingperformance.